Features of contemporary migration of the population of Ukraine: dynamics, directions, scale, problem - Czapliński, Paweł; Dzhaman, Vasyl (My University, 2023)
Population movement is an important factor in the socio-economic development of a country and its individual regions. Its geographical characteristics make it possible to identify, as quickly as possible, areas of depopulation and those where population flows clearly increase local and regional resources. In stable conditions, this provides an opportunity for a well-considered migration policy; in emergency situations, this becomes very difficult. The problems of contemporary migration geography in Ukraine are particularly relevant and painful in the context of Russia’s military attack and invasion of the territory of sovereign Ukraine in 2014 and a full-scale war since 24 February 2022. The aim of this article is to attempt to characterize migration in Ukraine, outlining the causes, directions, scale, intensity and dynamics of the processes over as broad a time horizon as possible, with a focus on the two sub-periods 2007–2013 and 2014–2021. Data for 2014–2021 are presented without taking into account the temporarily occupied territory of the Autonomous Republic of Crimea, the city of Sevastopol and part of the temporarily occupied territories in the Luhansk and Donetsk regions, as these data are not available. According to the study, the number of migrants who crossed the state border of Ukraine only after Russia launched a full-scale war against Ukraine (UN data as of 15.11.2022) amounted to 15.3 million people, of whom 7.6 million remained abroad
Keywords: migrations; Ukrainians; war